KELALAIAN YANG MENYEBABKAN KEBAKARAN DALAM HUKUM PIDANA DI KOTA SAMARINDA - Hamka Hamka (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT This study aims to determine the factors that cause fires based on the perception of the Fire Department of Samarinda City and the people of Samarinda City and legal sanctions against the perpetrators of criminal acts of negligence at the Fire Department of Samarinda City. Legal Studies Program, Faculty of Law, University of 17 August 1945 Samarinda.The results of this study states that the fire that occurred from January 2016 to April 2017 is still with the numbers up and down. The fires caused by negligence. However, most fires occur due to short-circuit problems in electrical installations and neglect in doing housework. As for the legal sanctions themselves still use the consultation techniques to the parties cause fire. The data used are primary data and secondary data. Primary data is obtained directly from the field by using questionnaires while secondary data obtained from government agencies associated with the research Office Fire Department.